1998
DOI: 10.2105/ajph.88.2.285
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of developmental dysplasia of the hip in The Netherlands: the validity of a standardized assessment protocol in infants.

Abstract: OBJECTIVES: This study evaluated the validity of the traditionally recommended screening protocol for developmental dysplasia of the hip in infants. METHODS: Study children (n = 1968) underwent a standardized screening examination. RESULTS: The incidence of developmental dysplasia of the hip was 3.7%. The sensitivity of the test protocol was 86%, the specificity was 82%, and the predictive values of positive and negative tests were 16% and 99%, respectively. CONCLUSIONS: The validity of the screening protocol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 10 publications
0
39
0
4
Order By: Relevance
“…In Table 6 the results of our study are compared with data on PPV and false positives published in studies on the following screening programmes: screening for phenylketonuria (PKU) and congenital hypothyroidism (CHT) by neonatal blood examination,5 6 screening for perceptive hearing impairments with the Ewing distraction test,7 screening for congenital heart malformations by physical examination,8 screening for idiopathic adolescent scoliosis by the standard forward bending test,9 and screening for developmental dysplasia of the hip by detection of limitations of hip abduction and differences in the length of the legs 10. The data are presented in order of increasing incidence of the relevant disorder.…”
Section: Discussionmentioning
confidence: 99%
“…In Table 6 the results of our study are compared with data on PPV and false positives published in studies on the following screening programmes: screening for phenylketonuria (PKU) and congenital hypothyroidism (CHT) by neonatal blood examination,5 6 screening for perceptive hearing impairments with the Ewing distraction test,7 screening for congenital heart malformations by physical examination,8 screening for idiopathic adolescent scoliosis by the standard forward bending test,9 and screening for developmental dysplasia of the hip by detection of limitations of hip abduction and differences in the length of the legs 10. The data are presented in order of increasing incidence of the relevant disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, only a minority (10 -27%) of all infants diagnosed with DDH in population-based studies have identified risk factors (with the exception of female gender), 30,32,33,35 and among those with risk factors, between 1% and 10% have DDH. 30,33,35 This wide range illustrates the impact of the reference standard on the relative importance of risk factors. Those studies with a more strict standard for diagnosing "true" DDH (eg, limited to those patients who receive treatment) demonstrate substantially lower rates of DDH among those with risk factors.…”
Section: Keymentioning
confidence: 94%
“…Primary care-based and population-based cohort studies [26][27][28][29][30][31][32][33][34][35][36] that include Ն1 of the major risk factors are summarized in Table 1. Consistently, only a minority (10 -27%) of all infants diagnosed with DDH in population-based studies have identified risk factors (with the exception of female gender), 30,32,33,35 and among those with risk factors, between 1% and 10% have DDH.…”
Section: Keymentioning
confidence: 99%
“…Instead, children are screened much later during periodic physical examinations in the child health care programme, which include assessment of the abduction range of the hips and the length of the legs 11. In the Sophia Childrens Hospital in Rotterdam, treatment policy is expectant: splinting is postponed until spontaneous recovery has become very unlikely.…”
Section: Examples Of Patient Follow Up Screening Evaluations In Childmentioning
confidence: 99%